(untitled) (Innovative professional education, 2025)
The article deals with the problem of developing critical thinking and media literacy of students as an important component of the professional competence of teachers of general education disciplines. Based on the analysis of the essence of the concepts of critical thinking and media literacy, their importance in the modern information society is substantiated. The role of teachers in the formation of these skills is outlined, the main components of their professional competence in this area are defined: cognitive, activity, motivational and value, and reflective. Effective strategies and methods for developing critical thinking and media literacy of students are presented